THE STRATEGY OF FORMULATE-SHARE-LISTEN-CREATE TO IMPROVE VOCATIONAL HIGH SCHOOL STUDENTS’ MATHEMATICAL PROBLEM POSING ABILITY AND MATHEMATICAL DISPOSITION ON PROBABILITY CONCEPT - Tina Rosyana; M. Afrilianto; Eka Senjayawati (Jurnal Infinity, 2018)
This study aims to examine the improvement of students’ mathematical problem posing ability and mathematical disposition through the strategy of Formulate-Share-Listen-Create (FSLC) on probability concept. The method used in this research is the experimental method, with the design of pretest-posttest control group. The population is all students of the vocational high school in Cimahi, while the sample was selected two classes from one of the vocational high school selected at random. The instrument of a test in the form of description is used to measure students’ mathematical problem posing ability, while the non-test instrument is questionnaire of mathematical disposition scale. The results showed (1) The mathematical problems posing of the students who obtained FSLC learning strategy is better than that of those who obtained conventional one; (2) The improvement of mathematical problems posing of the students who obtained FSLC learning strategy is better than that of those who obtained conventional one; (3) The mathematical disposition of students who obtained  FSLC learning strategy is better than that of those who obtained conventional learning.